Hyaluronic acid injection in the auricular base for the aesthetic correction of lying ears: A retrospective study - Zhezhen Xiong; Zhengzheng Jiang; Yaping Bai; Minxue Liang; Weitai Jiang; Kai Liu (Chinese Journal of Plastic and Reconstructive Surgery, 2023)
Background: Ears play an important role in facial profiles. Lying ears are not perceived favorably in Asian cultures; therefore, surgical procedures are implemented to adjust this defect. However, surgery has complications and requires recovery time. We introduced a hyaluronic acid (HA) injection technique to aesthetically improve ear prominence. Methods: This retrospective study examined 25 Chinese patients aged 20–47 years with congenital lying ears who received HA injections in the auricular base at Shanghai Ninth People’s Hospital and Hangzhou Yijie Medical Cosmetology Clinic between November 2019 and December 2022. The average injection volume was 6.32 ​± ​1.22 mL in the auricular base unilaterally, and the follow-up time ranged from 6 to 24 months. Morphological measurement data were recorded. Two-dimensional (2D) and three-dimensional (3D) images were obtained to evaluate the effects. Results: All patients showed improvements in ear prominence. The cranioauricular angle (CAA) increased from 22.24° ​± ​4.53° to 65.90° ​± ​5.38° immediately post-injection and was maintained at 49.18° ​± ​4.74° 6 months later. The ear projection (EP) increased from 14.75 ​± ​2.72 mm to 26.26 ​± ​2.94 mm immediately post-injection and was 22.51 ​± ​2.68 mm after 6 months. No serious complications were noted. Conclusion: HA injection in the auricular base effectively corrected the lying ears and aesthetically optimized the facial profile. It also had a face-lift effect that made the face look younger and more compact. The injection procedure was minimally invasive and required no recovery period. The effect was maintained for a long time and was satisfactory.